Acod1-mediated inhibition of aerobic glycolysis suppresses osteoclast differentiation and attenuates bone erosion in arthritis - Kachler, Katerina; Andreev, Darja; Thapa, Shreeya; Royzman, Dmytro; Gießl, Andreas; Karuppusamy, Shobika; Llerins Perez, Mireia; Liu, Mengdan; Hofmann, Jörg; Geßner, Arne; Meng, Xianyi; Rauber, Simon; et al. (Annals of the Rheumatic Diseases, 2024)
Objectives: Metabolic changes are crucially involved in osteoclast development and may contribute to bone degradation in rheumatoid arthritis (RA). The enzyme aconitate decarboxylase 1 (Acod1) is known to link the cellular function of monocyte-derived macrophages to their metabolic status. As osteoclasts derive from the monocyte lineage, we hypothesised a role for Acod1 and its metabolite itaconate in osteoclast differentiation and arthritis-associated bone loss. Methods: Itaconate levels were measured in human peripheral blood mononuclear cells (PBMCs) of patients with RA and healthy controls by mass spectrometry. Human and murine osteoclasts were treated with the itaconate derivative 4-octyl-itaconate (4-OI) in vitro. We examined the impact of Acod1-deficiency and 4-OI treatment on bone erosion in mice using K/BxN serum-induced arthritis and human TNF transgenic (hTNFtg) mice. SCENITH and extracellular flux analyses were used to evaluate the metabolic activity of osteoclasts and osteoclast progenitors. Acod1-dependent and itaconate-dependent changes in the osteoclast transcriptome were identified by RNA sequencing. CRISPR/Cas9 gene editing was used to investigate the role of hypoxia-inducible factor (Hif)-1α in Acod1-mediated regulation of osteoclast development. Results: Itaconate levels in PBMCs from patients with RA were inversely correlated with disease activity. Acod1-deficient mice exhibited increased osteoclast numbers and bone erosion in experimental arthritis while 4-OI treatment alleviated inflammatory bone loss in vivo and inhibited human and murine osteoclast differentiation in vitro. Mechanistically, Acod1 suppressed osteoclast differentiation by inhibiting succinate dehydrogenase-dependent production of reactive oxygen species and Hif1α-mediated induction of aerobic glycolysis. Conclusion: Acod1 and itaconate are crucial regulators of osteoclast differentiation and bone loss in inflammatory arthritis.
CRIS-Team Scopus Importer:2024-07-26
Keywords: Arthritis; Experimental; Arthritis; Rheumatoid; Bone Density; Inflammation; Osteoporosis

Alcohol-sourced acetate impairs T cell function by promoting cortactin acetylation - Azizov, Vugar; Hübner, Michel; Frech, Michael; Hofmann, Jörg; Kubankova, Marketa; Lapuente, Dennis; Tenbusch, Matthias; Guck, Jochen; Schett, Georg; Zaiss, Mario (iScience, 2023)
Alcohol is among the most widely consumed dietary substances. Excessive alcohol consumption damages the liver, heart, and brain. Alcohol also has strong immunoregulatory properties. Here, we report how alcohol impairs T cell function via acetylation of cortactin, a protein that binds filamentous actin and facilitates branching. Upon alcohol consumption, acetate, the metabolite of alcohol, accumulates in lymphoid organs. T cells exposed to acetate, exhibit increased acetylation of cortactin. Acetylation of cortactin inhibits filamentous actin binding and hence reduces T cell migration, immune synapse formation and activation. While mutated, acetylation-resistant cortactin rescues the acetate-induced inhibition of T cell migration, primary mouse cortactin knockout T cells exhibited impaired migration. Acetate-induced cytoskeletal changes effectively inhibited activation, proliferation, and immune synapse formation in T cells in vitro and in vivo in an influenza infection model in mice. Together these findings reveal cortactin as a possible target for mitigation of T cell driven autoimmune diseases.
CRIS-Team Scopus Importer:2023-07-21
Keywords: Immunology; Molecular biology

Altering Trehalose-6-Phosphate Content in Transgenic Potato Tubers Affects Tuber Growth and Alters Responsiveness to Hormones during Sprouting - Debast, Stefan; Nunes-Nesi, Adriano; Hajirezaei, Mohammad R.; Hofmann, Jörg; Sonnewald, Uwe; Fernie, Alisdair R.; Börnke, Frederik (Plant Physiology, 2011)
Trehalose-6-phosphate (T6P) is a signaling metabolite that regulates carbon metabolism, developmental processes, and growth in plants. In Arabidopsis (Arabidopsis thaliana), T6P signaling is, at least in part, mediated through inhibition of the SNF1-related protein kinase SnRK1. To investigate the role of T6P signaling in a heterotrophic, starch-accumulating storage organ, transgenic potato (Solanum tuberosum) plants with altered T6P levels specifically in their tubers were generated. Transgenic lines with elevated T6P levels (B33-TPS, expressing Escherichia coli osmoregulatory trehalose synthesis A [OtsA], which encodes a T6P synthase) displayed reduced starch content, decreased ATP contents, and increased respiration rate diagnostic for high metabolic activity. On the other hand, lines with significantly reduced T6P (B33-TPP, expressing E. coli OtsB, which encodes a T6P phosphatase) showed accumulation of soluble carbohydrates, hexose phosphates, and ATP, no change in starch when calculated on a fresh weight basis, and a strongly reduced tuber yield. [C-14] Glucose feeding to transgenic tubers indicated that carbon partitioning between starch and soluble carbohydrates was not altered. Transcriptional profiling of B33-TPP tubers revealed that target genes of SnRK1 were strongly up-regulated and that T6P inhibited potato tuber SnRK1 activity in vitro. Among the SnRK1 target genes in B33-TPP tubers, those involved in the promotion of cell proliferation and growth were down-regulated, while an inhibitor of cell cycle progression was up-regulated. T6P-accumulating tubers were strongly delayed in sprouting, while those with reduced T6P sprouted earlier than the wild type. Early sprouting of B33-TPP tubers correlated with a reduced abscisic acid content. Collectively, our data indicate that T6P plays an important role for potato tuber growth.

Cassava Metabolomics and Starch Quality - Rosado-Souza, Laise; David, Laure C.; Drapal, Margit; Fraser, Paul D.; Hofmann, Jörg; Klemens, Patrick A.W.; Ludewig, Frank; Neuhaus, H. Ekkehard; Obata, Toshihiro; Perez-Fons, Laura; Schlereth, Armin; Sonnewald, Uwe; et al. (Current Protocols in Plant Biology, 2019)
Cassava plays an important role as a staple food for more than 800 million people in the world due to its ability to maintain relatively high productivity even in nutrient-depleted soils. Even though cassava has been the focus of several breeding programs and has become a strong focus of research in the last few years, relatively little is currently known about its metabolism and metabolic composition in different tissues. In this article, the absolute content of sugars, organic acids, amino acids, phosphorylated intermediates, minerals, starch, carotenoids, chlorophylls, tocopherols, and total protein as well as starch quality is described based on multiple analytical techniques, with protocols specifically adjusted for material from different cassava tissues. Moreover, quantification of secondary metabolites relative to internal standards is presented using both non-targeted and targeted metabolomics approaches. The protocols have also been adjusted to apply to freeze-dried material in order to allow processing of field harvest samples that typically will require long-distance transport. © 2019 The Authors. Basic Protocol 1: Metabolic profiling by gas chromatography-mass spectrometry (GC-MS) Support Protocol 1: Preparation of freeze-dried cassava material Support Protocol 2: Preparation of standard compound mixtures for absolute quantification of metabolites by GC-MS Support Protocol 3: Preparation of retention-time standard mixture Basic Protocol 2: Determination of organic acids and phosphorylated intermediates by ion chromatography-mass spectrometry (IC-MS) Support Protocol 4: Preparation of standards and recovery experimental procedure Basic Protocol 3: Determination of soluble sugars, starch, and free amino acids Alternate Protocol: Determination of soluble sugars and starch Basic Protocol 4: Determination of anions Basic Protocol 5: Determination of elements Basic Protocol 6: Determination of total protein Basic Protocol 7: Determination of non-targeted and targeted secondary metabolites Basic Protocol 8: Determination of carotenoids, chlorophylls, and tocopherol Basic Protocol 9: Determination of starch quality.
CRIS-Team Scopus Importer:2019-12-24
Keywords: chemotypes; Manihot esculenta; metabolite classification; metabolite profiling; metabolomics

Cellular and extracellular proteome of the animal pathogen corynebacterium silvaticum, a close relative of zoonotic corynebacterium ulcerans and corynebacterium pseudotuberculosis - Möller, Jens; Schorlemmer, Svenja; Hofmann, Jörg; Burkovski, Andreas (Proteomes, 2020)
Corynebacterium silvaticum is a newly described animal pathogen, closely related to the emerging human pathogen Corynebacterium ulcerans and Corynebacterium pseudotuberculosis, a major pathogen of small ruminants. In this study, proteins of a whole cell and a shaving fraction and the exoproteome of C. silvaticum strain W25 were analyzed as a first proteome study of this species. In total, 1305 proteins were identified out of 2013 proteins encoded by the W25 genome sequence and number of putative virulence factors were detected already under standard growth conditions including phospholipase D and sialidase. An up to now uncharacterized trypsin-like protease is by far the most secreted protein in this species, indicating a putative role in pathogenicity. Furthermore, the proteome analyses carried out in this study support the recently published taxonomical delineation of C. silvaticum from the closely related zoonotic Corynebacterium species.
CRIS-Team Scopus Importer:2020-09-11
Keywords: Exoproteome; LC-MS/MS; Mass spectrometry; Necrotizing lymphadenitis; Secretome; Trypsin-like serine protease; Zoonosis

Choline transporter-like1 (CHER1) is crucial for plasmodesmata maturation in Arabidopsis thaliana - Kraner, Max; Link, Katrin; Melzer, Michael; Ekici, Arif Bülent; Uebe, Steffen; Tarazona, Pablo; Feussner, Ivo; Hofmann, Jörg; Sonnewald, Uwe (Plant Journal, 2016)
Plasmodesmata (PD) are microscopic pores connecting plant cells and enable cell-to-cell transport. Currently, little is known about the molecular mechanisms regulating PD formation and development. To uncover components of PD development we made use of the 17 kDa movement protein (MP17) encoded by the Potato leafroll virus (PLRV). The protein is required for cell-to-cell movement of the virus and localises to complex PD. Forward genetic screening for Arabidopsis mutants with altered PD-binding of MP17 revealed several mutant lines, while molecular genetics, biochemical and microscopic studies allowed further characterisation. Map-based cloning of one mutant revealed a point mutation in the choline transporter-like 1 (CHER1) protein, changing glycine(247) into glutamate. Mutation in CHER1 resulted in a starch excess phenotype and stunted growth. Ultrastructure analysis of shoot apical meristems, developing and fully developed leaves showed reduced PD numbers and the absence of complex PD in fully developed leaves. This indicates that cher1 mutants are impaired in PD formation and development. Global lipid profiling revealed only slight modifications in the overall lipid composition, however, altered composition of PD-associated lipids cannot be ruled out. Thus, cher1 is devoid of complex PD in developed leaves and provides insights into the formation of complex PD at the molecular level. This article is protected by copyright. All rights reserved.
EVALuna2:9344

Common motifs in the response of cereal primary metabolism to fungal pathogens are not based on similar transcriptional reprogramming - Voll, Lars; Horst, Robin; Voitsik, Anna Maria; Zajic, Doreen; Samans, Birgit; Pons-Kuehnemann, Joern; Doehlemann, Gunther; Muench, Steffen; Wahl, Ramon; Molitor, Alexandra; Hofmann, Jörg; Schmiedl, Alfred; et al. (Frontiers in Plant Science, 2011)
During compatible interactions with their host plants, biotrophic plant-pathogens subvert host metabolism to ensure the sustained provision of nutrient assimilates by the colonized host cells. To investigate, whether common motifs can be revealed in the response of primary carbon and nitrogen metabolism toward colonization with biotrophic fungi in cereal leaves, we have conducted a combined metabolome and transcriptome study of three quite divergent pathosystems, the barley powdery mildew fungus (Blumeria graminis f.sp. hordei), the corn smut fungus Ustilago maydis, and the maize anthracnose fungus Colletotrichum graminicola, the latter being a hemibiotroph that only exhibits an initial biotrophic phase during its establishment. Based on the analysis of 42 water-soluble metabolites, we were able to separate early biotrophic from late biotrophic interactions by hierarchical cluster analysis and principal component analysis, irrespective of the plant host. Interestingly, the corresponding transcriptome dataset could not discriminate between these stages of biotrophy, irrespective, of whether transcript data for genes of central metabolism or the entire transcriptome dataset was used. Strong differences in the transcriptional regulation of photosynthesis, glycolysis, the TCA cycle, lipid biosynthesis, and cell wall metabolism were observed between the pathosystems. However, increased contents of Gln, Asn, and glucose as well as diminished contents of PEP and 3-PGA were common to early post-penetration stages of all interactions. On the transcriptional level, genes of the TCA cycle, nucleotide energy metabolism and amino acid biosynthesis exhibited consistent trends among the compared biotrophic interactions, identifying the requirement for metabolic energy and the rearrangement of amino acid pools as common transcriptional motifs during early biotrophy. Both metabolome and transcript data were employed to generate models of leaf primary metabolism during early biotrophy for the three investigated interactions.
Keywords: maize; barley; Ustilago maydis; Blumeria graminis f.sp hordei; Colletotrichum graminicola; compatible interaction; metabolite analysis; transcriptome analysis

Corynebacterium diphtheriae proteome adaptation to cell culture medium and serum - Möller, Jens; Nosratabadi, Fatemeh; Musella, Luca; Hofmann, Jörg; Burkovski, Andreas (Proteomes, 2021)
Host-pathogen interactions are often studied in vitro using primary or immortal cell lines. This set-up avoids ethical problems of animal testing and has the additional advantage of lower costs. However, the influence of cell culture media on bacterial growth and metabolism is not considered or investigated in most cases. To address this question growth and proteome adaptation of Corynebacterium diphtheriae strain ISS3319 were investigated in this study. Bacteria were cultured in standard growth medium, cell culture medium, and fetal calf serum. Mass spectrometric analyses and label-free protein quantification hint at an increased bacterial pathogenicity when grown in cell culture medium as well as an influence of the growth medium on the cell envelope.
CRIS-Team Scopus Importer:2021-04-09
Keywords: Diphtheria; Host-pathogen interaction; Label-free quantification; Metabolic pathway; Proteomics

Crop genetic diversity uncovers metabolites, elements, and gene networks predicted to be associated with high plant biomass yields in maize - Hajheidari, Mohsen; Gerlach, Nina; Dorau, Kristof; Amin Omidbakhshfard, M.; Pesch, Lina; Hofmann, Jörg; Hallab, Asis; Ponce-Soto, Gabriel Y.; Kuhalskaya, Anastasiya; Medeiros, David B.; Bourceret, Amélia; Usadel, Björn; et al. (PNAS Nexus, 2022)
Rapid population growth and increasing demand for food, feed, and bioenergy in these times of unprecedented climate change require breeding for increased biomass production on the world s croplands. To accelerate breeding programs, knowledge of the relationship between biomass features and underlying gene networks is needed to guide future breeding efforts. To this end, large-scale multiomics datasets were created with genetically diverse maize lines, all grown in long-term organic and conventional cropping systems. Analysis of the datasets, integrated using regression modeling and network analysis revealed key metabolites, elements, gene transcripts, and gene networks, whose contents during vegetative growth substantially influence the build-up of plant biomass in the reproductive phase. We found that S and P content in the source leaf and P content in the root during the vegetative stage contributed the most to predicting plant performance at the reproductive stage. In agreement with the Gene Ontology enrichment analysis, the cis-motifs and identified transcription factors associated with upregulated genes under phosphate deficiency showed great diversity in the molecular response to phosphate deficiency in selected lines. Furthermore, our data demonstrate that genotype-dependent uptake, assimilation, and allocation of essential nutrient elements (especially C and N) during vegetative growth under phosphate starvation plays an important role in determining plant biomass by controlling root traits related to nutrient uptake. These integrative multiomics results revealed key factors underlying maize productivity and open new opportunities for efficient, rapid, and cost-effective plant breeding to increase biomass yield of the cereal crop maize under adverse environmental factors.
CRIS-Team Scopus Importer:2024-12-16
Keywords: biomass; gene networks; ionome; metabolome; systems biology

Crystal Structure of the Extracellular Domain of the Human Dendritic Cell Surface Marker CD83 - Heilingloh, Christiane; Klingl, Stefan; Egerer-Sieber, Claudia; Schmid, Benedikt; Weiler, Sigrid; Mühl-Zürbes, Petra; Hofmann, Jörg; Stump, Joachim; Sticht, Heinrich; Kummer, Mirko; Steinkasserer, Alexander; Muller, Yves (Journal of Molecular Biology, 2017)
Keywords: homotypic interactions; immune co-stimulation and -suppression; structure–function relationships; V-set Ig-domain; X-ray crystallography

Detecting functional groups of Arabidopsis mutants by metabolic profiling and evaluation of pleiotropic responses - Hofmann, Jörg; Börnke, Frederik; Schmiedl, Alfred; Kleine, Tatjana; Sonnewald, Uwe (Frontiers in Plant Science, 2011)
Metabolic profiles and fingerprints of Arabidopsis thaliana plants with various defects in plastidic sugar metabolism or photosynthesis were analyzed to elucidate if the genetic mutations can be traced by comparing their metabolic status. Using a platform of chromatographic and spectrometric tools data from untargeted full MS scans as well as from selected metabolites including major carbohydrates, phosphorylated intermediates, carboxylates, free amino acids, major antioxidants, and plastidic pigments were evaluated. Our key observations are that by multivariate statistical analysis each mutant can be separated by a unique metabolic signature. Closely related mutants come close. Thus metabolic profiles of sugar mutants are different but more similar than those of photosynthesis mutants. All mutants show pleiotropic responses mirrored in their metabolic status. These pleiotropic responses are typical and can be used for separating and grouping of the mutants. Our findings show that metabolite fingerprints can be taken to classify mutants and hence may be used to sort genes into functional groups.
Keywords: metabolic profiling; fingerprinting; functional genomics; Arabidopsis thaliana; pleiotropic response; chloroplast

Dietary short-term fiber interventions in arthritis patients increase systemic scfa levels and regulate inflammation - Dürholz, Kerstin; Hofmann, Jörg; Iljazovic, Aida; Häger, Julian; Lucas, Sébastien; Sarter, Kerstin; Strowig, Till; Bang, Holger; Rech, Jürgen; Schett, Georg; Zaiss, Mario (Nutrients, 2020)
Chronic inflammatory diseases are often initiated and guided by the release of proinflammatory mediators. Rheumatoid arthritis (RA) is caused by an imbalance between the pro-and anti-inflammatory mediators in the joints, thereby favoring chronic inflammation and joint damage. Here, we investigate if short-term high-fiber dietary intervention shifts this towards anti-inflammatory mediators. Healthy controls (n = 10) and RA patients (n = 29) under routine care received daily high-fiber bars for 15 or 30 days, respectively. Stool and sera were analyzed for pro-and anti-inflammatory mediators. A high-fiber dietary intervention resulted in increased anti-inflammatory short-chain fatty acids (SCFA), decreased proarthritic cytokine concentrations, along with a durable shift in the Firmicutes-to-Bacteroidetes ratio. Together, these results further strengthen high-fiber dietary interventions as a practical approach complementing existing pharmacological therapies.
CRIS-Team Scopus Importer:2020-10-30
Keywords: High-fiber diet (HFD); Microbial metabolites; Short chain fatty acids (SCFA)

Efficient sugar utilization and transition from oxidative to substrate-level phosphorylation in high starch storage roots of African cassava genotypes - Lamm, Christian; Rabbi, Ismail Y.; Medeiros, David Barbosa; Rosado-Souza, Laise; Pommerrenig, Benjamin; Dahmani, Ismail; Rüscher, David; Hofmann, Jörg; van Doorn, Anna M.; Schlereth, Armin; Neuhaus, H. Ekkehard; Fernie, Alisdair R.; et al. (Plant Journal, 2023)
Cassava's storage roots represent one of the most important sources of nutritional carbohydrates worldwide. Particularly, smallholder farmers in sub-Saharan Africa depend on this crop plant, where resilient and yield-improved varieties are of vital importance to support steadily increasing populations. Aided by a growing understanding of the plant's metabolism and physiology, targeted improvement concepts already led to visible gains in recent years. To expand our knowledge and to contribute to these successes, we investigated storage roots of eight cassava genotypes with differential dry matter content from three successive field trials for their proteomic and metabolic profiles. At large, the metabolic focus in storage roots transitioned from cellular growth processes toward carbohydrate and nitrogen storage with increasing dry matter content. This is reflected in higher abundance of proteins related to nucleotide synthesis, protein turnover, and vacuolar energization in low starch genotypes, while proteins involved in sugar conversion and glycolysis were more prevalent in high dry matter genotypes. This shift in metabolic orientation was underlined by a clear transition from oxidative- to substrate-level phosphorylation in high dry matter genotypes. Our analyses highlight metabolic patterns that are consistently and quantitatively associated with high dry matter accumulation in cassava storage roots, providing fundamental understanding of cassava's metabolism as well as a data resource for targeted genetic improvement.
CRIS-Team Scopus Importer:2023-07-21
Keywords: energy metabolism; glycolysis; Manihot esculenta; metabolomics; oxidative phosphorylation; proteomics; source/sink; starch metabolism; sugar metabolism; TCA-cycle

Ethanol consumption decreases autoantibody titers by blocking IL-21 secretion of Tfh cells during the development of arthritis - Azizov, Vugar; Dietel, K.; Kolenbrander, A.; Seubert, S.; Steffen, F.; Meidenbauer, J.; Steffen, Ulrike; Hofmann, Jörg; Nimmerjahn, Falk; Linker, R.; Wirtz, Stefan; Sarter-Zaiss, Kerstin; et al. (EUROPEAN JOURNAL OF IMMUNOLOGY, 2019)
CRIS-Team WoS Importer:2019-10-08

Ethanol consumption inhibits TFH cell responses and the development of autoimmune arthritis - Azizov, Vugar; Dietel, Katharina; Steffen, Franziska; Dürholz, Kerstin; Meidenbauer, Julia; Lucas, Sébastien; Frech, Michael; Omata, Yasunori; Tajik, Narges; Knipfer, Lisa; Kolenbrander, Anne; Seubert, Silvia; et al. (Nature Communications, 2020)
Alcohol consumption is a consistent protective factor for the development of autoimmune diseases such as rheumatoid arthritis (RA). The underlying mechanism for this tolerance-inducing effect of alcohol, however, is unknown. Here we show that alcohol and its metabolite acetate alter the functional state of T follicular helper (TFH) cells in vitro and in vivo, thereby exerting immune regulatory and tolerance-inducing properties. Alcohol-exposed mice have reduced Bcl6 and PD-1 expression as well as IL-21 production by TFH cells, preventing proper spatial organization of TFH cells to form TFH:B cell conjugates in germinal centers. This effect is associated with impaired autoantibody formation, and mitigates experimental autoimmune arthritis. By contrast, T cell independent immune responses and passive models of arthritis are not affected by alcohol exposure. These data clarify the immune regulatory and tolerance-inducing effect of alcohol consumption.
CRIS-Team Scopus Importer:2020-05-05

Genome-wide transcriptome analysis of Clavibacter michiganensis subsp. michiganensis grown in xylem mimicking medium - Hiery, Eva; Adam, Susanne; Reid, Stephen; Hofmann, Jörg; Sonnewald, Sophia; Burkovski, Andreas (Journal of Biotechnology, 2013)

Hop/Sti1-A Two-Faced Cochaperone Involved in Pattern Recognition Receptor Maturation and Viral Infection - Lamm, Christian; Kraner, Max; Hofmann, Jörg; Boernke, Frederik; Mock, Hans-Peter; Sonnewald, Uwe (Frontiers in Plant Science, 2017)
Perception of pathogens by host pattern recognition receptors (PRRs) or R proteins is a prerequisite to promote successful immune responses. The Hsp70/Hsp90 organizing protein Hop/Sti1, a multifunctional cochaperone, has been implicated in the maturation of a receptor-like kinase (RLK) necessary for chitin sensing. However, it remains unknown whether Hop/Sti1 is generally participating in PRR genesis. Using RNA-interference (RNAi), we silenced Hop/Sti1 expression in Nicotiana tabacum to gain further insight into the role of the cochaperone in plant defense responses. As expected, transgenic plants do not respond to chitin treatment anymore. In contrast to this, trafficking and functionality of the flagellin PRR FLS2 were unaltered, suggesting a selective involvement of Hop/Sti1 during PRR maturation. Furthermore, Hop/Sti1 was identified as a cellular determinant of Potato virus Y (PVY) symptom development in tobacco, since PVY was able to accumulate to near wild-type level without provoking the usual veinal necrosis phenotype. In addition, typical antiviral host defense responses were suppressed in the transgenic plants. These data suggest that perception of PVY is dependent on Hop/Sti1-mediated receptor maturation, while viral symptoms represent a failing attempt to restrict PVY spread. In addition, Hop/Sti1 colocalized with virus-induced membrane aggregates in wild-type plants. The retention of Hop/Sti1 in potential viral replication complexes suggests a role during viral translation/replication, explaining why RNAi-lines do not exhibit increased susceptibility to PVY. This study provides evidence for a dual role of Hop/Sti1 in PRR maturation and pathogen perception as well as in promoting viral proliferation.
Keywords: Hop/Sti1 cochaperone; pattern recognition receptor; CERK1; FLS2; pathogen perception; Nicotiana tabacum cv. Samsun NN; Potato virus Y

Hop/Sti1 - A Two-Faced Cochaperone Involved in Pattern Recognition Receptor Maturation and Viral Infection. - Lamm, Christian; Kraner, Max; Hofmann, Jörg; Boernke, Frederik; Mock, Hans-Peter; Sonnewald, Uwe (Frontiers in Plant Science, 2017)
Perception of pathogens by host pattern recognition receptors (PRRs) or R proteins is a prerequisite to promote successful immune responses. The Hsp70/Hsp90 organizing protein Hop/Sti1, a multifunctional cochaperone, has been implicated in the maturation of a receptor-like kinase (RLK) necessary for chitin sensing. However, it remains unknown whether Hop/Sti1 is generally participating in PRR genesis. Using RNA-interference (RNAi), we silenced Hop/Sti1 expression in Nicotiana tabacum to gain further insight into the role of the cochaperone in plant defense responses. As expected, transgenic plants do not respond to chitin treatment anymore. In contrast to this, trafficking and functionality of the flagellin PRR FLS2 were unaltered, suggesting a selective involvement of Hop/Sti1 during PRR maturation. Furthermore, Hop/Sti1 was identified as a cellular determinant of Potato virus Y (PVY) symptom development in tobacco, since PVY was able to accumulate to near wild-type level without provoking the usual veinal necrosis phenotype. In addition, typical antiviral host defense responses were suppressed in the transgenic plants. These data suggest that perception of PVY is dependent on Hop/Sti1-mediated receptor maturation, while viral symptoms represent a failing attempt to restrict PVY spread. In addition, Hop/Sti1 colocalized with virus-induced membrane aggregates in wild-type plants. The retention of Hop/Sti1 in potential viral replication complexes suggests a role during viral translation/replication, explaining why RNAi-lines do not exhibit increased susceptibility to PVY. This study provides evidence for a dual role of Hop/Sti1 in PRR maturation and pathogen perception as well as in promoting viral proliferation.

IL-33-induced metabolic reprogramming controls the differentiation of alternatively activated macrophages and the resolution of inflammation - Faas, Maria; Ipseiz, Natacha; Ackermann, Jochen; Culemann, Stephan; Grüneboom, Anika; Schröder, Fenja; Rothe, Tobias; Scholtysek, Carina; Eberhardt, Martin; Böttcher, Martin; Kirchner, Philipp; Stoll, Cornelia; et al. (Immunity, 2021)
Alternatively activated macrophages (AAMs) contribute to the resolution of inflammation and tissue repair. However, molecular pathways that govern their differentiation have remained incompletely understood. Here, we show that uncoupling protein-2-mediated mitochondrial reprogramming and the transcription factor GATA3 specifically controlled the differentiation of pro-resolving AAMs in response to the alarmin IL-33. In macrophages, IL-33 sequentially triggered early expression of pro-inflammatory genes and subsequent differentiation into AAMs. Global analysis of underlying signaling events revealed that IL-33 induced a rapid metabolic rewiring of macrophages that involved uncoupling of the respiratory chain and increased production of the metabolite itaconate, which subsequently triggered a GATA3-mediated AAM polarization. Conditional deletion of GATA3 in mononuclear phagocytes accordingly abrogated IL-33-induced differentiation of AAMs and tissue repair upon muscle injury. Our data thus identify an IL-4-independent and GATA3-dependent pathway in mononuclear phagocytes that results from mitochondrial rewiring and controls macrophage plasticity and the resolution of inflammation.
CRIS-Team Scopus Importer:2021-11-19
Keywords: alternatively activated macrophage; GATA3; interleukin-33; itaconate; mitochondrial rewiring; resolution of inlammation; UCP2; uncoupling

Macrophage phosphoproteome analysis reveals MINCLE-dependent and-independent mycobacterial cord factor signaling - Hansen, Madlen; Peltier, Julian; Killy, Barbara; Amin, Bushra; Bodendorfer, Barbara; HäRtlova, Anetta; Uebel, Sebastian; Bosmann, Markus; Hofmann, Jörg; Büttner, Christian; Ekici, Arif Bülent; Kuttke, Mario; et al. (Molecular & Cellular Proteomics, 2019)
Immune sensing of Mycobacterium tuberculosis relies on recognition by macrophages. Mycobacterial cord factor, trehalose-6,6-dimycolate (TDM), is the most abundant cell wall glycolipid and binds to the C-type lectin receptor (CLR) MINCLE. To explore the kinase signaling linking the TDM-MINCLE interaction to gene expression, we employed quantitative phosphoproteome analysis. TDM caused upregulation of 6.7% and suppressed 3.8% of the 14,000 phospho-sites identified on 3727 proteins. MINCLE-dependent phosphorylation was observed for canonical players of CLR signaling (e.g. PLC, PKC), and was enriched for PKC and GSK3 kinase motifs. MINCLE-dependent activation of the PI3K-AKT-GSK3 pathway contributed to inflammatory gene expression and required the PI3K regulatory subunit p85. Unexpectedly, a substantial fraction of TDM-induced phosphorylation was MINCLE-independent, a finding paralleled by transcriptome data. Bioinformatics analysis of both data sets concurred in the requirement for MINCLE for innate immune response pathways and processes. In contrast, MINCLE-independent phosphorylation and transcriptome responses were linked to cell cycle regulation. Collectively, our global analyses show substantial reprogramming of macrophages by TDM and reveal a dichotomy of MINCLE-dependent and-independent signaling linked to distinct biological responses.
CRIS-Team Scopus Importer:2019-05-02

Maize Field Study Reveals Covaried Microbiota and Metabolic Changes in Roots over Plant Growth - Bourceret, Amelia; Guan, Rui; Dorau, Kristof; Mansfeldt, Tim; Omidbakhshfard, Amin; Medeiros, David B.; Fernie, Alisdair R.; Hofmann, Jörg; Sonnewald, Uwe; Mayer, Jochen; Gerlach, Nina; Bucher, Marcel; et al. (Mbio, 2022)
Plant roots are colonized by microorganisms from the surrounding soil that belong to different kingdoms and form a multikingdom microbial community called the root microbiota. Despite their importance for plant growth, the relationship between soil management, the root microbiota, and plant performance remains unknown. Here, we characterize the maize root-associated bacterial, fungal, and oomycetal communities during the vegetative and reproductive growth stages of four maize inbred lines and the pht1;6 phosphate transporter mutant. These plants were grown in two long-term experimental fields under four contrasting soil managements, including phosphate-deficient and -sufficient conditions. We showed that the maize root-associated microbiota is influenced by soil management and changes during host growth stages. We identified stable bacterial and fungal root-associated taxa that persist throughout the host life cycle. These taxa were accompanied by dynamic members that covary with changes in root metabolites. We observed an inverse stable-to-dynamic ratio between root-associated bacterial and fungal communities. We also found a host footprint on the soil biota, characterized by a convergence between soil, rhizosphere, and root bacterial communities during reproductive maize growth. Our study reveals the spatiotemporal dynamics of the maize rootassociated microbiota and suggests that the fungal assemblage is less responsive to changes in root metabolites than the bacterial community.
CRIS-Team Scopus Importer:2022-05-13
Keywords: maize; phosphate; phosphate metabolism; plant-microbe interaction; root metabolome; root microbiota; soil management

Mass Spectrometric Characterization of HSV-1 L-Particles From Human Dendritic Cells and BHK21 Cells and Analysis of Their Functional Role - Birzer, Alexandra; Kraner, Max; Heilingloh, Christiane Silke; Mühl-Zürbes, Petra; Hofmann, Jörg; Steinkasserer, Alexander; Popella, Linda (Frontiers in Microbiology, 2020)
Herpes simplex virus type 1 (HSV-1) is a very common human pathogenic virus among the world’s population. The lytic replication cycle of HSV-1 is, amongst others, characterized by a tripartite viral gene expression cascade, the assembly of nucleocapsids involving their subsequent nuclear egress, tegumentation, re-envelopment and the final release of progeny viral particles. During productive infection of a multitude of different cell types, HSV-1 generates not only infectious heavy (H-) particles, but also non-infectious light (L-) particles, lacking the capsid. In monocyte-derived mature dendritic cells (mDCs), HSV-1 causes a non-productive infection with the predominant release of L-particles. Until now, the generation and function of L-particles is not well understood, however, they are described as factors transferring viral components to the cellular microenvironment. To obtain deeper insights into the L-particle composition, we performed a mass-spectrometry-based analysis of L-particles derived from HSV-1-infected mDCs or BHK21 cells and H-particles from the latter one. In total, we detected 63 viral proteins in both H- and L-particle preparations derived from HSV-1-infected BHK21 cells. In L-particles from HSV-1-infected mDCs we identified 41 viral proteins which are differentially distributed compared to L-particles from BHK21 cells. In this study, we present data suggesting that L-particles modify mDCs and suppress their T cell stimulatory capacity. Due to the plethora of specific viral proteins incorporated into and transmitted by L-particles, it is tempting to speculate that L-particles manipulate non-infected bystander cells for the benefit of the virus.
CRIS-Team Scopus Importer:2020-10-23
Keywords: BHK21 cells; dendritic cells; heavy particles; HSV-1; immunomodulatory effect; light particles; mass spectrometry; T cell stimulation

Metabolic reprogramming of osteoclasts represents a therapeutic target during the treatment of osteoporosis - Taubmann, Jule; Krishnacoumar, Brenda; Böhm, Christina; Faas, Maria; Müller, Dorothea; Adam, Susanne; Stoll, Cornelia; Böttcher, Martin; Mougiakakos, Dimitrios; Sonnewald, Uwe; Hofmann, Jörg; Schett, Georg; et al. (Scientific Reports, 2020)
Osteoclasts are specialised bone resorbing cells that control both physiological and pathological bone turnover. Functional changes in the differentiation and activity of osteoclasts are accompanied by active metabolic reprogramming. However, the biological significance and the in vivo relevance of these events has remained unclear. Here we show that bone resorption of differentiated osteoclasts heavily relies on increased aerobic glycolysis and glycolysis-derived lactate production. While pharmacological inhibition of glycolysis did not affect osteoclast differentiation or viability, it efficiently blocked bone resorption in vitro and in vivo and consequently ameliorated ovariectomy-induced bone loss. Our experiments thus highlight the therapeutic potential of interfering with osteoclast-intrinsic metabolic pathways as possible strategy for the treatment of diseases characterized by accelerated bone loss.
CRIS-Team Scopus Importer:2020-12-11

Metabolic rewiring promotes anti-inflammatory effects of glucocorticoids - Auger, Jean-Philippe; Zimmermann, Max; Faas, Maria; Stifel, Ulrich; Chambers, David; Krishnacoumar, Brenda; Taudte, R. Verena; Grund, Charlotte; Erdmann, Gitta; Scholtysek, Carina; Uderhardt, Stefan; Ben Brahim, Oumaima; et al. (Nature, 2024)
Glucocorticoids represent the mainstay of therapy for a broad spectrum of immune-mediated inflammatory diseases. However, the molecular mechanisms underlying their anti-inflammatory mode of action have remained incompletely understood1. Here we show that the anti-inflammatory properties of glucocorticoids involve reprogramming of the mitochondrial metabolism of macrophages, resulting in increased and sustained production of the anti-inflammatory metabolite itaconate and consequent inhibition of the inflammatory response. The glucocorticoid receptor interacts with parts of the pyruvate dehydrogenase complex whereby glucocorticoids provoke an increase in activity and enable an accelerated and paradoxical flux of the tricarboxylic acid (TCA) cycle in otherwise pro-inflammatory macrophages. This glucocorticoid-mediated rewiring of mitochondrial metabolism potentiates TCA-cycle-dependent production of itaconate throughout the inflammatory response, thereby interfering with the production of pro-inflammatory cytokines. By contrast, artificial blocking of the TCA cycle or genetic deficiency in aconitate decarboxylase 1, the rate-limiting enzyme of itaconate synthesis, interferes with the anti-inflammatory effects of glucocorticoids and, accordingly, abrogates their beneficial effects during a diverse range of preclinical models of immune-mediated inflammatory diseases. Our findings provide important insights into the anti-inflammatory properties of glucocorticoids and have substantial implications for the design of new classes of anti-inflammatory drugs.
CRIS-Team Scopus Importer:2024-04-19

Mitochondrial respiration in B lymphocytes is essential for humoral immunity by controlling the flux of the TCA cycle - Urbanczyk, Sophia; Baris, Olivier R.; Hofmann, Jörg; Taudte, Verena; Guegen, Naïg; Golombek, Florian; Castiglione, Kathrin; Meng, Xianyi; Bozec, Aline; Thomas, Jana; Weckwerth, Leonie; Mougiakakos, Dimitrios; et al. (Cell Reports, 2022)
To elucidate the function of oxidative phosphorylation (OxPhos) during B cell differentiation, we employ CD23Cre-driven expression of the dominant-negative K320E mutant of the mitochondrial helicase Twinkle (DNT). DNT-expression depletes mitochondrial DNA during B cell maturation, reduces the abundance of respiratory chain protein subunits encoded by mitochondrial DNA, and, consequently, respiratory chain super-complexes in activated B cells. Whereas B cell development in DNT mice is normal, B cell proliferation, germinal centers, class switch to IgG, plasma cell maturation, and T cell-dependent as well as T cell-independent humoral immunity are diminished. DNT expression dampens OxPhos but increases glycolysis in lipopolysaccharide and B cell receptor-activated cells. Lipopolysaccharide-activated DNT-B cells exhibit altered metabolites of glycolysis, the pentose phosphate pathway, and the tricarboxylic acid cycle and a lower amount of phosphatidic acid. Consequently, mTORC1 activity and BLIMP1 induction are curtailed, whereas HIF1α is stabilized. Hence, mitochondrial DNA controls the metabolism of activated B cells via OxPhos to foster humoral immunity.
CRIS-Team Scopus Importer:2022-06-17
Keywords: B lymphocyte; class switch recombination; CP: Immunology; germinal center; HIF1; hypoxia inducible factor 1; mammalian target of Rapamycin; mitochondrial DNA; mitochondrial respiration; mTOR; oxidative phosphorylation; phosphatidic acid; plasma cell; TCA cycle

Multi-Omics of Corynebacterium Pseudotuberculosis 12CS0282 and an In Silico Reverse Vaccinology Approach Reveal Novel Vaccine and Drug Targets - Möller, Jens; Bodenschatz, Mona; Sangal, Vartul; Hofmann, Jörg; Burkovski, Andreas (Proteomes, 2022)
Corynebacterium pseudotuberculosis is an important animal pathogen, which is also able to infect humans. An optimal treatment of infections with this pathogen is not available today and consequently, more research is necessary to understand the infection process. Here, we present a combined -omics and bioinformatics approach to characterize C. pseudotuberculosis 12CS0282. The genome sequence of strain 12CS0282 was determined, analyzed in comparison with the available 130 C. pseudotuberculosis sequences and used as a basis for proteome analyses. In a reverse vaccinology approach, putative vaccine and drug targets for 12CS0208 were identified. Mass spectrometry analyses revealed the presence of multiple virulence factors even without host contact. In macrophage interaction studies, C. pseudotuberculosis 12CS0282 was highly resistant against human phagocytes and even multiplied within human THP-1 cells. Taken together, the data indicate a high pathogenic potential of the strain.
CRIS-Team WoS Importer:2023-01-13

Propionate induced bacterial-derived histamine promotes resolution of synovial inflammation - Dürholz, Kerstin; Lucas, Sébastien; Schmid, Eva; Schaelter, F.; Frech, Michael; Azizov, Vugar; Hofmann, Jörg; Iljazovic, A.; Strowig, T.; Taudte, Verena; Fromm, Martin; Xiang, Wei; et al. (EUROPEAN JOURNAL OF IMMUNOLOGY, 2022)
CRIS-Team WoS Importer:2023-01-27

Short chain fatty acids are potent regulators of systemic bone mass and protect for pathological bone loss by inhibiting osteoclasts - Lucas, S.; Omata, Y.; Böttcher, Martin; Hofmann, Jörg; Krishnacoumar, B.; Krönke, Gerhard; Mougiakakos, Dimitrios; Iljazovic, A.; Sonnewald, Uwe; Strowig, T.; Schett, Georg; Zaiss, Mario (European Journal of Immunology, 2017)

Short-chain fatty acids regulate systemic bone mass and protect from pathological bone loss - Lucas, Sebastien; Omata, Yasunori; Hofmann, Jörg; Böttcher, Martin; Iljazovic, Aida; Sarter, Kerstin; Albrecht, Olivia; Schulz, Oscar; Krishnacoumar, Brenda; Krönke, Gerhard; Herrmann, Martin; Mougiakakos, Dimitrios; et al. (Nature Communications, 2018)
Microbial metabolites are known to modulate immune responses of the host. The main metabolites derived from microbial fermentation of dietary fibers in the intestine, short-chain fatty acids (SCFA), affect local and systemic immune functions. Here we show that SCFA are regulators of osteoclast metabolism and bone mass in vivo. Treatment of mice with SCFA as well as feeding with a high-fiber diet significantly increases bone mass and prevents postmenopausal and inflammation-induced bone loss. The protective effects of SCFA on bone mass are associated with inhibition of osteoclast differentiation and bone resorption in vitro and in vivo, while bone formation is not affected. Mechanistically, propionate (C3) and butyrate (C4) induce metabolic reprogramming of osteoclasts resulting in enhanced glycolysis at the expense of oxidative phosphorylation, thereby downregulating essential osteoclast genes such as TRAF6 and NFATc1. In summary, these data identify SCFA as potent regulators of osteoclast metabolism and bone homeostasis.
EVALuna2:13520

Surface and Extracellular Proteome of the Emerging Pathogen Corynebacterium ulcerans - Bittel, Miriam; Gastiger, Susanne; Amin, Bushra; Hofmann, Jörg; Burkovski, Andreas (Proteomes, 2018)

The plastid outer envelope protein OEP16 affects metabolic fluxes during ABA-controlled seed development and germination - Pudelski, Birgit; Schock, Annette; Hoth, Stefan; Radchuk, Ruslana; Weber, Hans; Hofmann, Jörg; Sonnewald, Uwe; Soll, Jurgen; Philippar, Katrin (Journal of Experimental Botany, 2012)
Previously, the OEP16.1 channel pore in the outer envelope membrane of mature pea (Pisum sativum) chloroplasts in vitro has been characterized to be selective for amino acids. Isolation of OEP16.2, a second OEP16 isoform from pea, in the current study allowed membrane localization and gene expression of OEP16 to be followed throughout seed development and germination of Arabidopsis thaliana and P. sativum. Thereby it can be shown on the transcript and protein level that the isoforms OEP16.1 and OEP16.2 in both plant species are alternating: whereas OEP16.1 is prominent in early embryo development and first leaves of the growing plantlet, OEP16.2 dominates in late seed development stages, which are associated with dormancy and desiccation, as well as early germination events. Further, OEP16.2 expression in seeds is under control of the phytohormone abscisic acid (ABA), leading to an ABA-hypersensitive phenotype of germinating oep16 knockout mutants. In consequence, the loss of OEP16 causes metabolic imbalance, in particular that of amino acids during seed development and early germination. It is thus concluded that in vivo OEP16 most probably functions in shuttling amino acids across the outer envelope of seed plastids.
Keywords: Abscisic acid; amino acid transport; Arabidopsis; outer envelope protein; pea; plastid; seed development; seed metabolite content

The short-chain fatty acid pentanoate suppresses autoimmunity by modulating the metabolic-epigenetic crosstalk in lymphocytes - Luu, Maik; Pautz, Sabine; Kohl, Vanessa; Singh, Rajeev; Romero, Rossana; Lucas, Sebastien; Hofmann, Jörg; Raifer, Hartmann; Vachharajani, Niyati; Carrascosa, Lucia Campos; Lamp, Boris; Nist, Andrea; et al. (Nature Communications, 2019)
Short-chain fatty acids (SCFAs) have immunomodulatory effects, but the underlying mechanisms are not well understood. Here we show that pentanoate, a physiologically abundant SCFA, is a potent regulator of immunometabolism. Pentanoate induces IL-10 production in lymphocytes by reprogramming their metabolic activity towards elevated glucose oxidation. Mechanistically, this reprogramming is mediated by supplying additional pentanoate-originated acetyl-CoA for histone acetyltransferases, and by pentanoate-triggered enhancement of mTOR activity. In experimental mouse models of colitis and multiple sclerosis, pentanoate-induced regulatory B cells mediate protection from autoimmune pathology. Additionally, pentanoate shows a potent histone deacetylase-inhibitory activity in CD4(+) T cells, thereby reducing their IL-17A production. In germ-free mice monocolonized with segmented filamentous bacteria (SFB), pentanoate inhibits the generation of small-intestinal Th17 cells and ameliorates SFB-promoted inflammation in the central nervous system. Taken together, by enhancing IL-10 production and suppressing Th17 cells, the SCFA pentanoate might be of therapeutic relevance for inflammatory and autoimmune diseases.
CRIS-Team WoS Importer:2019-02-27

Transcriptome and metabolome profiling of field-grown transgenic barley lack induced differences but show cultivar-specific variances - Kogel, Karl-Heinz; Voll, Lars; Schaefer, Patrick; Jansen, Carin; Wu, Yongchun; Langen, Gregor; Imani, Jafargholi; Hofmann, Jörg; Schmiedl, Alfred; Sonnewald, Sophia; Von Wettstein, Diter; Cook, R. James; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2010)
The aim of the present study was to assess possible adverse effects of transgene expression in leaves of field-grown barley relative to the influence of genetic background and the effect of plant interaction with arbuscular mycorrhizal fungi. We conducted transcript profiling, metabolome profiling, and metabolic fingerprinting of wild-type accessions and barley transgenics with seed-specific expression of (1,3-1, 4)-beta-glucanase (GluB) in Baronesse (B) as well as of transgenics in Golden Promise (GP) background with ubiquitous expression of codon-optimized Trichoderma harzianum endochitinase (ChGP). We found more than 1,600 differential transcripts between varieties GP and B, with defense genes being strongly overrepresented in B, indicating a divergent response to subclinical pathogen challenge in the field. In contrast, no statistically significant differences between ChGP and GP could be detected based on transcriptome or metabolome analysis, although 22 genes and 4 metabolites were differentially abundant when comparing GluB and B, leading to the distinction of these two genotypes in principle component analysis. The coregulation of most of these genes in GluB and GP, as well as simple sequence repeat-marker analysis, suggests that the distinctive alleles in GluB are inherited from GP. Thus, the effect of the two investigated transgenes on the global transcript pro. le is substantially lower than the effect of a minor number of alleles that differ as a consequence of crop breeding. Exposing roots to the spores of the mycorrhizal Glomus sp. had little effect on the leaf transcriptome, but central leaf metabolism was consistently altered in all genotypes.
Keywords: food safety; glucanase; chitinase; sustainability

Ustilago maydis Infection Strongly Alters Organic Nitrogen Allocation in Maize and Stimulates Productivity of Systemic Source Leaves - Horst, Robin; Doehlemann, Gunther; Wahl, Ramon; Hofmann, Jörg; Schmiedl, Alfred; Kahmann, Regine; Kaemper, Joerg; Sonnewald, Uwe; Voll, Lars (Plant Physiology, 2010)
The basidiomycete Ustilago maydis is the causal agent of corn smut disease and induces tumor formation during biotrophic growth in its host maize (Zea mays). We have conducted a combined metabolome and transcriptome survey of infected leaves between 1 d post infection (dpi) and 8 dpi, representing infected leaf primordia and fully developed tumors, respectively. At 4 and 8 dpi, we observed a substantial increase in contents of the nitrogen-rich amino acids glutamine and asparagine, while the activities of enzymes involved in primary nitrogen assimilation and the content of ammonia and nitrate were reduced by 50% in tumors compared with mock controls. Employing stable isotope labeling, we could demonstrate that U. maydis-induced tumors show a reduced assimilation of soil-derived (NO3-)-N-15 and represent strong sinks for nitrogen. Specific labeling of the free amino acid pool of systemic source leaves with [N-15] urea revealed an increased import of organic nitrogen from systemic leaves to tumor tissue, indicating that organic nitrogen provision supports the formation of U. maydis-induced tumors. In turn, amino acid export from systemic source leaves was doubled in infected plants. The analysis of the phloem amino acid pool revealed that glutamine and asparagine are not transported to the tumor tissue, although these two amino acids were found to accumulate within the tumor. Photosynthesis was increased and senescence was delayed in systemic source leaves upon tumor development on infected plants, indicating that the elevated sink demand for nitrogen could determine photosynthetic rates in source leaves.